DEVELOPMENT OF POWTOON-BASED AUDIO-VISUAL LEARNING MEDIA TO IMPROVE STUDENTS' CREATIVE THINKING ABILITY ON STRAIGHT-MOTION MATERIALS - Maghfirah Zulfa; Muliani Muliani; Halimatus Sakdiah; Syafrizal Idris; Fajrul Wahdi Ginting (Universitas Labuhanbatu, 2023)
Research on the development of Powtoon-based audio-visual learning media aims to determine the feasibility of the product and to see whether there is an increase in students' creative thinking abilities in straight-motion material and to see student responses and teacher responses. This study uses the type of Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study were questionnaires and tests, and the research subjects consisted of class X MAN 3 North Aceh. The results showed that the audio-visual learning media that had been developed was declared feasible and could improve students' creative thinking skills based on assessments: 1) The media expert obtained a percentage of 80.56% according to the criteria of